2021
DOI: 10.1186/s13058-021-01430-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism for OSM-promoted extracellular matrix remodeling in breast cancer: LOXL2 upregulation and subsequent ECM alignment

Abstract: Background Invasive ductal carcinoma (IDC) is a serious problem for patients as it metastasizes, decreasing 5-year patient survival from > 95 to ~ 27%. The breast tumor microenvironment (TME) is often saturated with proinflammatory cytokines, such as oncostatin M (OSM), which promote epithelial-to-mesenchymal transitions (EMT) in IDC and increased metastasis. The extracellular matrix (ECM) also plays an important role in promoting invasive and metastatic potential of IDC. Specifically, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…We additionally identify in this study macrophages and OSM as important players in this interplay. Interestingly, Dinca et al recently showed in invasive breast ductal carcinomas that OSM can induce LOXL2 expression, which in turn promotes an increase in ECM collagen I fibre crosslinking, leading to increased cell invasion 59. Likewise, Lee et al, recently demonstrated that MØ-secreted Osm induces inflammatory gene expression in CAFs, creating a pro-tumourigenic environment in PDAC 60.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally identify in this study macrophages and OSM as important players in this interplay. Interestingly, Dinca et al recently showed in invasive breast ductal carcinomas that OSM can induce LOXL2 expression, which in turn promotes an increase in ECM collagen I fibre crosslinking, leading to increased cell invasion 59. Likewise, Lee et al, recently demonstrated that MØ-secreted Osm induces inflammatory gene expression in CAFs, creating a pro-tumourigenic environment in PDAC 60.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, OSM can promote tumor progression. Overexpression of OSM and OSMR has been detected in various cancers, including gastric, colorectal, breast, and glioma [ 38 , 39 ]. OSM-OSMR signal transduction plays a vital role in inflammation, oxidative stress, hematopoiesis, and development and is increasingly considered an essential factor in tumor progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased cell surface concentration of these receptors results in enhanced sensitivity to EGF family ligands, which, in turn, enhances tumor growth and tumor metastasis [ 42 ]. Following these observations, additional evidence has accumulated suggesting that lysyl oxidases, such as LOXL2 and LOX, promote desmoplasia under various conditions and, as a result, promote tumor cells invasiveness and tumor metastasis [ 43 , 44 , 45 , 46 , 47 ]. Furthermore, interference with collagen stabilization by the inhibition of lysyl oxidases significantly enhances responses to chemotherapy in various tumor models, even in metastatic disease [ 48 ].…”
Section: Extracellular Mechanisms By Which Lysyl Oxidases Promote Tum...mentioning
confidence: 99%